AN ANALYSIS ON THE USE OF LEXICAL COHESION IN STUDENTS’ WRITING - Zulianti, Hajjah (Lentera: Jurnal Ilmiah Kependidikan, 2018)
This research aims to describe the lexical cohesion used in students’ writing, and to find out the highest frequency of lexical ties in students’ writing. In conducting the research, the researcher uses descriptive qualitative method. The researcher uses a documentation to collect the data. The data are the students’ scientific writing tasks on fifth semester at STKIP PGRI Bandar Lampung. In analyzing the data, the researcher uses the procedure such as recording the data in the data card, categorizing the data based on the types of lexical cohesion, summing up the total number of lexical cohesion frequencies, describing the data and drawing conclusion. The result shows that the types of lexical cohesion in students’ writing are repetition, synonymy, antonymy, and meronymy. Repetiton becomes the prominent types of lexical cohesion used in students’ writing. Meanwhile the hyponymy is the lowest frequency of occurrence in their writings